Rancang Bangun Sistem Informasi Akuntansi dan Perpajakan Berbasis Web Pada Koperasi Karyawan Sejahtera - Gilang Saputra Ramadhan; Hardiansyah Hardiansyah; Ilham Ilham; Sri Nirmala Sari (Politeknik Bosowa, 2021)
Koperasi Karyawan Sejahtera are Operatives located in the bosowa polytechnik ward with businesses selling food and drink in the campus area and selling student uniforms. The cooperation will need ease with current financial management using manual logging. Apart from excessive timekeeping, manual logging is considered less efficient in regard to data safety. Based on this, this study has one goal: To know the right computer-based accounting system for welfare workers; To build a financial information system on a prosperous employee cooperative; To find out the extent of this financial information system can help the logging process on welfare workers; And to know the results of the feasibility test of web-based financial information systems using iso 9126 standardized approaches of functionality, usability and portability aspects. The research method is research and development which is the research method used to generate new product design, test the effectiveness of existing products, and develop and create new products. The results of this study are the proper recording system for computer-based financial statements for cooperatives is a recording system with the cash basis method, namely a method that focuses on the cash income and expenditure of the cooperative. This information system is built using the Waterfall development model which consists of several stages, namely the Analysis Stage, the Design Stage, the Testing and Implementation Phase and Program Maintenance. The results of the feasibility test of this system which was carried out using the ISO 9126 standardization approach from the aspects of Functionality, Usability and Portability showed that the system was feasible and ready to use. This information system is implemented using transactions owned by cooperatives and in its application, this system is very helpful for employees in terms of their work.